A Method for Measuring the Relative Taxation of Families - Wertz, Kenneth L. (The Review of Economics and Statistics, 1978)
16-17 year olds, or both, we estimate that these differentials would increase total teenage employment. amount of the increase is largely conjectural, since error variances in estimated parameters are large. For example, we estimate a two-standard-deviation upper bound for increased teenage employment of roughly 5% for a differential of 1.60-1.28 extended to the 14-15 year-old group, and an upper bound increase of 10% if the same differential is extended to all those 14-17 years old. lower bound in each case is roughly zero, so that a reduction in total teenage employment seems unlikely. An important question of differentials is the effect on employment of those groups to whom the differential is not extended. For a differential extended to 14-15 year-old workers, we estimate virtually no effect on employment of those 16-19 years old. substitution effects are nullified by scale effects. For a more broadly based 1.601.28 differential extended to those 14-17, the range of uncertainty concerning employment of those 18-19 is large, encompassing reductions and increases of 5%. REFERENCES Allen, R.G.D., Mathematical Analysis for Economists (New York: St. Martins Press, 1938). Hashimoto, Masanori, and Jacob Mincer, Employment and Effects of unpublished manuscript, National Bureau of Economic Research, April 1970. Kosters, Marvin, and Finis Welch, The Effects of Wages on the Distribution of Changes in Aggregate Employment, American Economic Review 62 (June 1972), 323-332. Mincer, Jacob, Unemployment Effects of Journal of Political Economy 84, part 2 (Aug. 1976), 87-104. Parsons, Donald, The Cost of School Time, Foregone Earnings, and Human Capital Formulation, unpublished manuscript, Ohio State University, Feb. 1973. Siskind, Frederic B., Minimum Wage Legislation in the United States: Comment, Economic Inquiry 15 (Jan. 1977), 135-138. U.S. Department of Labor, Bureau of Labor Statistics, Youth and Wages, Bulletin 1657 (1970). Welch, Finis, Minimum Wage Legislation in the United States, Economic Inquiry 12 (Sept. 1974), 285-318. Minimum Wage Legislation in the United States: Reply, Economic Inquiry 15 (Jan. 1977), 139-142.